The Jordan Education Initiative : A Multi-Stakeholder Partnership Model to Support Education Reform - Bannayan, Haif; Guaqueta, Juliana; Obeidat, Osama; Patrinos, Harry Anthony; Porta, Emilio (World Bank, Washington, DC, 2012)
The Jordan Education Initiative, launched in 2003 under the umbrella of the World Economic Forum, is a public-private partnership, or multi-stakeholder partnership, that integrates information and communication technologies into the education process as a tool for teaching and learning in grades 1-12. This initiative fits within the ongoing reform of the education system in Jordan that began in the 1990s. The Jordan Education Initiative's main objective is to help Jordanian students develop critical knowledge economy skills crucial for competitiveness and economic growth. The Initiative also seeks to build the capacity of the local information technology industry for the development of innovative learning solutions, and to build a sustainable model of reform supported by the private sector that could be scaled nationally and replicated in other developing countries.